Dovlatov and surroundings a philological novel - Genis, Aleksandr Aleksandrovič 1953- (Academic Studies Press, 2023)
Dovlatov and Surroundings is a literary ode by one of the most consequential late 20th-century Russian writers, Alexander Genis, to another: Sergei Dovlatov. Though the book's focus is ostensibly the man himself, the text unfolds as a comprehensive look at the Soviet, post-Soviet, and American cultures that shaped him and which he shaped. Dovlatov and Surroundings constantly, but effortlessly shifts its focus from the intimate to the sweeping, as Genis's reflections on his friendship with Dovlatov organically give way to recollections about diaspora life, which transition smoothly into analyses of language, culture, politics, and literature. Characterized by Genis as an obituary, this book makes plain the significance of Dovlatov to Russian literature and the nuances of the Soviet cultural heritage